2020
DOI: 10.3390/ijms21041208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Involved in the Impairment of Boar Sperm Motility by Peroxynitrite-Induced Nitrosative Stress

Abstract: Excessive levels of reactive nitrogen species (RNS) produce nitrosative stress. Among RNS is peroxynitrite, a highly reactive free radical generated when nitric oxide reacts with superoxide anion. Peroxynitrite effects have been mainly studied in somatic cells, and in spermatozoa the majority of studies are focused in humans. The aim of this study is to investigate the in vitro peroxynitrite effect on boar spermatozoa functions and the molecular mechanisms involved. Spermatozoa were exposed to the donor 3-morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The difference in the results could be attributed to the fact that, in our study, the positive effect might be masked by the presence of additionally induced oxidative stress. The reaction of NO with ROS results in the formation of peroxynitrite, which impairs sperm quality traits and the state of lipid peroxidation in boar spermatozoa at micromolar concentrations [ 24 ]. An interesting observation was made concerning the kinetic parameters of the CASA analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the results could be attributed to the fact that, in our study, the positive effect might be masked by the presence of additionally induced oxidative stress. The reaction of NO with ROS results in the formation of peroxynitrite, which impairs sperm quality traits and the state of lipid peroxidation in boar spermatozoa at micromolar concentrations [ 24 ]. An interesting observation was made concerning the kinetic parameters of the CASA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Current RS classification includes reactive oxygen species (ROS), reactive nitrogen species (RNS), and reactive sulfur species (RSS), whereof the last two named groups also involve both gasotransmitters, NO and H 2 S. As an example, in a recent study by Zhang et al [ 21 ], the negative impact of elevated concentrations of H 2 S on boar sperm motility was observed. Moreover, the presence of oxidative stress can potentiate the negative impact of high gasotransmitter levels, such as in the case of NO [ 6 ], which forms peroxynitrite that inhibits mitochondrial activity [ 22 ], reduces sperm motility [ 23 ], and increases lipid peroxidation of boar sperm membrane [ 24 ]. Thus, the effect of the gasotransmitter on sperm functionality and structural integrity depends not only on its concentration, but also on the specific cellular microenvironment and the presence of other RS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Uribe et al [90] observed mitochondrial permeability transition (MPT) under nitrosative stress with biochemical traits of MPT-driven necrosis. On the contrary, Serrano et al [91] found that, although peroxinitrite induces oxidative stress in boar sperm, leading to lipid peroxidation and motility loss, it does not affect mitochondrial membrane potential.…”
Section: The Role Of No and H 2 S In Oxidative Stressmentioning
confidence: 94%